Corporate social responsibility and product market power - Chong-Chuo Chang; Han Yang; Kun-Zhan Hsu (Economies, 2022)
This study explores the impact of corporate social responsibility (CSR) on the product market power by examining listed firms on the Taiwan Stock Exchange and Taipei Exchange from 2005 to 2017. We use CSR awards as a social responsibility indicator, and the results show a positive relationship between CSR and excess price-cost margins (market share), supporting the thesis that firms that value CSR activities can strengthen the competitive advantage of products in the market.
Keywords: 330; corporate social responsibility; excess price-cost margin; market share; product market power